Heavy metal bioaccumulation in different fish species in the coast of the Persian Gulf, Iran. (2nd October 2015) - Pilehvarian, Ali Asghar; Malekirad, Ali Akbar; Bolandnazar, Najmeh-Sadat; Rezaei, Mohammad
Abstract: This study project aimed to determine the concentrations of five heavy metals (Al, As, Cd, Hg and Pb) in different fish species in the coast of the Persian Gulf in Iran. Ninety samples divided to three types' fish including Rastrelliger kanagurta, Tenualosa ilisha and Scomberomorus commerson . The investigation performed by ICP-OES technique. The estimated daily intake of heavy metals compared with allowable daily intake of these. Also, the means compared with the allowable limit regulated by national Iranian standards. Results showed that the heavy metal contamination of these was in the standard limit, except Pb in R. kanagurta (43.33%), T. ilisha (23.33%) and S. commerson (13.3%) had greater than European Union limit (300 μg L −1 ). Therefore, monitoring of the heavy metals contents, specially Pb is very important yet because of the presence of these in soils due to increase of industrial activity and use pesticides and fertilizers.